2021
DOI: 10.3389/fonc.2021.674224
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Clinicopathological Feature and Prognosis of Young Gastric Cancer Patients Aged ≤ 45 Years Old

Abstract: PurposeThe aim of this retrospective study was to probe into clinicopathological features and prognosis of early-onset gastric cancer (EOGC) patients aged ≤ 45 years old.MethodsThis study selected 154 young gastric cancer patients aged ≤ 45 years old and 158 elderly gastric cancer patients aged > 50 years old admitted to West China Hospital of Sichuan University in 2009-2019 as the research object. These patients were further divided into two groups according to whether tumor can be resected radically. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
1
18
0
1
Order By: Relevance
“…In several cancer types, younger patients have been shown to have faster disease progression. [13][14][15][16] This may explain why younger age was found to increase the risk of switching to high-dose methadone. Moreover, outpatient status may have increased the risk of highdose switching for different reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several cancer types, younger patients have been shown to have faster disease progression. [13][14][15][16] This may explain why younger age was found to increase the risk of switching to high-dose methadone. Moreover, outpatient status may have increased the risk of highdose switching for different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, factors that decreased the risk included the concomitant use of NSAIDs and fentanyl as the pre‐switching opioid. In several cancer types, younger patients have been shown to have faster disease progression 13‐16 . This may explain why younger age was found to increase the risk of switching to high‐dose methadone.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that EOGC displays unique genomic features. For example, tumors of patients with EOGC are more likely to have a diffuse histologic subtype and include signet ring cells, more likely to contain mutated CDH1 , BANP , MUC5B , and TGFBR1 genes, and less likely to contain microsatellite instability [ 9 , 17 , 18 , 19 ]. While smoking and alcohol use are known modifiable risk factors for the development of gastric cancer, particularly in the US, where the prevalence of Helicobacter pylori infection is relatively low, modifiable risk factors such as smoking and alcohol use were not found to be associated with the development of EOGC in an analysis of the Behavioral Risk Factor Surveillance System [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these patients require special attention. According to Qian Huang et al, early-onset GC is associated with diffuse Lauren type and poorly differentiated tumors (19). Surprisingly, after adjusting for other variables, the degree of tumor differentiation was eventually excluded from our prediction nomogram.…”
Section: Radiationmentioning
confidence: 91%